2016
DOI: 10.1002/jcp.25586
|View full text |Cite
|
Sign up to set email alerts
|

Acute Ethanol Increases IGF‐I‐Induced Phosphorylation of ERKs by Enhancing Recruitment of p52‐Shc to the Grb2/Shc Complex

Abstract: Ethanol plays a detrimental role in the development of the brain. Multiple studies have shown that ethanol inhibits insulin-like growth factor I receptor (IGF-IR) function. Because the IGF-IR contributes to brain development by supporting neural growth, survival, and differentiation, we sought to determine the molecular mechanism(s) involved in ethanol’s effects on this membrane-associated tyrosine kinase. Using multiple neuronal cell types, we performed Western blot, immunoprecipitation, and GST-pulldowns fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
(75 reference statements)
1
1
0
Order By: Relevance
“…Thus, it seems that the pattern of alcohol administration has a larger effect on the hippocampal phosphoproteome than the dose of alcohol used, which could be related to the intermittent pattern of consumption−withdrawal that characterizes it, since this withdrawal alters the glutamatergic system, causing excitotoxicity, 59 although the mechanism by which hippocampal deficits occur after intermittent alcohol consumption is not fully known. Among the seven proteins identified, only GRB2-2 has been previously related to ethanol use 60 and our results showed an increase in the Low-I group compared to the M group. GRB2-2 is a multifunctional adaptor protein that links many different growth factor receptors and an important signal transducer for numerous receptor tyrosine kinases, 61 such as the PI3K/Akt pathway, 62 which, interestingly, is also affected by ethanol as shown in previous studies from our group.…”
Section: Discussionsupporting
confidence: 58%
“…Thus, it seems that the pattern of alcohol administration has a larger effect on the hippocampal phosphoproteome than the dose of alcohol used, which could be related to the intermittent pattern of consumption−withdrawal that characterizes it, since this withdrawal alters the glutamatergic system, causing excitotoxicity, 59 although the mechanism by which hippocampal deficits occur after intermittent alcohol consumption is not fully known. Among the seven proteins identified, only GRB2-2 has been previously related to ethanol use 60 and our results showed an increase in the Low-I group compared to the M group. GRB2-2 is a multifunctional adaptor protein that links many different growth factor receptors and an important signal transducer for numerous receptor tyrosine kinases, 61 such as the PI3K/Akt pathway, 62 which, interestingly, is also affected by ethanol as shown in previous studies from our group.…”
Section: Discussionsupporting
confidence: 58%
“…In fact, it has been shown that EtOH positively and negatively affects Akt phosphorylation at low and high doses, respectively, in hepatic insulin signaling in rats (77). Differential effects on IGF-1R activation based on the type of EtOH treatment (i.e., chronic exposure versus acute low-dose exposure) have also been reported in cultured neurons (79). Cilia-dependent IGF-1R signaling is required for cell-cycle progression in cortical progenitor cells (53,80) and the differentiation of preadipocytes (52).…”
Section: Neuroscience Discussionmentioning
confidence: 93%